2019
DOI: 10.1002/glia.23695
|View full text |Cite
|
Sign up to set email alerts
|

The role of microglia in ischemic preconditioning

Abstract: Ischemic preconditioning (IPC) is an experimental phenomenon in which a brief ischemic stimulus confers protection against a subsequent prolonged ischemic event. Initially thought to be due to mechanistic changes in neurons, our understanding of IPC has evolved to encompass a global reprogramming of the Central Nervous System (CNS) after transient ischemia/reperfusion that requires innate immune signaling pathways including Toll‐like receptors (TLRs) and Type I interferons. Microglia are the CNS resident neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 183 publications
3
30
0
Order By: Relevance
“…83 Studies implicate TLR4 activation leads to a number of downstream events that are necessary for the establishment of IPC and the microglial response to damage. 82 Supporting this idea, studies have shown that aged mice have increased microglial activity after injection of IL-1β and IL-12 into the hippocampus. 85 This phenomenon is known as microglia priming and can make the microglia susceptible to secondary inflammatory stimulus leading to an exaggerated inflammatory response after CNS injury.…”
Section: Crog Lial S E X D Ifferen Ce S During Ag Ingmentioning
confidence: 96%
See 3 more Smart Citations
“…83 Studies implicate TLR4 activation leads to a number of downstream events that are necessary for the establishment of IPC and the microglial response to damage. 82 Supporting this idea, studies have shown that aged mice have increased microglial activity after injection of IL-1β and IL-12 into the hippocampus. 85 This phenomenon is known as microglia priming and can make the microglia susceptible to secondary inflammatory stimulus leading to an exaggerated inflammatory response after CNS injury.…”
Section: Crog Lial S E X D Ifferen Ce S During Ag Ingmentioning
confidence: 96%
“…Microglia also play a role in ischemic preconditioning (IPC), which is protective against prolonged ischemic events. TLRs are some of the key signaling pathways in IPC reprogramming of the CNS . A study demonstrated that pretreatment with unmethylated CpG oligodeoxynucleotides (ODNs)—a ligand for Toll‐like receptor 9 (TLR9)—induces protection against ischemic brain damage in mice and nonhuman primates .…”
Section: Microglial Sex Differences During Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…Following a sublethal hypoxic-ischemic injury, activation of TLRs can cause a greater cerebral ischemic tolerance, a process called preconditioning. However, activation of TLRs after ischemia-induced tissue and cell injury can worsen tissue damage through the NF-kB signaling pathway [ 21 , 29 , 30 ]. TLRs and their downstream signaling molecules represent a relevant pharmacologic target for modulation of tolerance to an ischemic insult [ 31 ].…”
Section: Introductionmentioning
confidence: 99%